1996
DOI: 10.1038/380079a0
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activation by the E6 gene product of human papillomavirus type 16

Abstract: Activation of telomerase, a ribonucleoprotein complex that synthesizes telomere repeat sequences, is linked to cell immortalization and is characteristic of most cell lines and tumours. Here we show that expression of the human papillomavirus type 16 (HPV-16) E6 protein activates telomerase in early-passage human keratinocytes and mammary epithelial cells. This activation was observed in cells pre-crisis, that is, before they became immortal, and occurred within one passage of retroviral infection with vectors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

30
496
4
18

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 729 publications
(552 citation statements)
references
References 20 publications
30
496
4
18
Order By: Relevance
“…HPV 16 E6 has multiple activities and at least two appear to be relevant for immortalization: inactivation of the p53 protein (Liu et al, 1999b) and induction of telomerase (Klingelhutz et al, 1996). Interestingly, a subset of immortalizing E6 mutants that do not degrade p53 still target the hAda3 protein for degradation and inhibit p53-mediated transactivation (Kumar et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…HPV 16 E6 has multiple activities and at least two appear to be relevant for immortalization: inactivation of the p53 protein (Liu et al, 1999b) and induction of telomerase (Klingelhutz et al, 1996). Interestingly, a subset of immortalizing E6 mutants that do not degrade p53 still target the hAda3 protein for degradation and inhibit p53-mediated transactivation (Kumar et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, at least some E6 activities, such as activation of telomerase, appear to be cell-type dependent (Klingelhutz et al, 1996). These observations indicate that it is difficult to deduce the critical activities of E6 in HPV-positive cancer cells from the various effects observed after ectopic (over)expression of E6, in heterologous cell systems.…”
Section: Introductionmentioning
confidence: 99%
“…The de novo transcription of the hTERT gene is considered the dominant, rate-limiting step in telomerase activation whereas the expression of hTEP1 and hTR is constitutive [1,9]. The regulation of hTERT expression is complicated, and it has been reported that hTERT transcription can be activated by overexpression or activation of several transcription activators [8,17,20,24,33,36]. Several recent reports have identified c-myc binding sites (E-boxes) in the hTERT promoter and found that c-myc positively regulates hTERT expression [11,30].…”
Section: Introductionmentioning
confidence: 99%